Study on Provision of Drinking Water Infrastructure through Public-Private Partnerships Scheme (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The limited availability of drinking water and the local government budget in meeting the needs of drinking water as a service to the community's basic needs require the roles of the private sector or business entity. Based on the mandate of the Presidential Regulation of the Republic of Indonesia number 38 of 2015 concerning Government Cooperation with Business Entities and Infrastructure Provision, the needs of drinking water to the community can be fulfilled through the Public-Private Partnerships pattern. This study aimed to identify the factors influencing the provision of drinking water through the Public-Private Partnerships scheme and find leading factors to support local governments in preparing technical and non-technical conditions during supplying drinking water in the regions. The proposal for the Umbulan Drinking Water Supply System in East Java and Lembata Drinking Water Supply System in East Nusa Tenggara were evaluated. This research employed a comparative descriptive approach, where the data obtained from two regions were analyzed and compared using the variation finding comparison method. The study results showed that providing drinking water supply systems in two locations had several differences. The most influencing factors were the flow of raw water sources, the number of potential customers, service coverage, geographical conditions, and regional financial stability